An Analysis of Moral Message in Movie “LUCA” Using Semiotic Approach by Roland Barthes - Lalu Taufik Hasby Ash Shiddiq; Zainudin Abdussamad; Titik Ceriyani Miswaty (Humanitatis : Journal of Language and Literature, 2023)
This research explores the moral messages embedded in the animated movie "Luca" by Disney Pixar through a semiotic lens. Literary works, including films, serve as a medium to convey messages that entertain and impart moral values. In a world where reading rates are low, movies become a popular means of storytelling. The study draws on Roland Barthes' semiotic science to analyse signs and symbols within the movie, emphasizing the moral messages they convey. The chosen movie, "Luca," not only garnered critical acclaim and awards but also offers an entertaining narrative with positive messages about coexistence between different beings. The research methodology involves qualitative analysis, specifically descriptive qualitative methods, focusing on scenes and conversations to unveil moral messages. Thomas Lickona's moral education theory complements the analysis, emphasizing the importance of knowing, desiring, and doing good. The findings reveal seven types of moral messages: honesty, a helping attitude, kindness and caring, courage and self-confidence, self-control, teamwork, and hard work. The study contributes to understanding how animated movies, such as "Luca," convey essential moral values. While prior research has explored moral values in movies, this study uniquely integrates semiotics, enriching the understanding of the visual and symbolic elements conveying moral messages. The identified moral messages provide valuable insights for individuals seeking positive behavior models in their daily lives. Future research could expand the dataset and explore additional films to validate and extend these findings.